Information and Communication Aspects of Founding and Operating the Scientific Schools in the Field of Publishing and Printing - Semenyuk, E.P.; Kotlyarevsky, Ya.V.; Melnikov, O.V. (Science and Innovation, 2024)
Essential typological features of scientific schools are investigated, paying special attention to informational and communicational aspects of the problem. Peculiarities of scientific research organization in printing and publishing branches are revealed. A specific character of branch science consisting in the fact of close connection between scientific school formation and the activities of specialized higher education institutions is noted. The process of the establishment and development of the Lviv-Kyiv school of printing industry technologies, particularly regarding activities on development and application of photopolymer printing forms in printing production is analysed. On the example of the formation and the activity of the Lviv-Kyiv school of printing and publishing technologies the features of scientific school are listed. It is shown that scientific schools are formed under the influence of society demands, by the logic of science and practice development providing long-term fundamental and applied research and having essential achievements of public recognition in the homeland and abroad. Given this the functions of scientific schools are defined.